2015
DOI: 10.1007/s10549-015-3469-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of MED12 in fibroadenomas and phyllodes tumors of the breast by means of targeted next-generation sequencing

Abstract: We aimed to analyze MED12 mutation in fibroadenomas (FAs) and phyllodes tumors (PTs) of the breast, which are closely related and consist of epithelial and stromal components. Targeted deep-sequencing using next-generation sequencing was performed in FAs (n = 58) and PTs (n = 27). The frequency of MED12 mutant tumors was significantly higher (P = 0.016) in PTs (74.1 %) than in FAs. (46.6 %). As for FAs, this frequency was significantly higher (P = 0.001) for intracanalicular type (69.0 %) than for other histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 25 publications
5
37
2
Order By: Relevance
“…This could be due to the significant proportion of juvenile fibroadenomas (17 of 43) in our cohort, which showed a lower frequency of MED12 mutations of 35% compared with 56% in the conventional fibroadenoma group. This is consistent with the findings of other studies which demonstrated a higher frequency of MED12 mutations in tumours with an intracanalicular growth pattern, which is usually not a feature of juvenile fibroadenomas. One study reported a higher incidence of MED12 mutations in juvenile fibroadenomas (52.6%).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This could be due to the significant proportion of juvenile fibroadenomas (17 of 43) in our cohort, which showed a lower frequency of MED12 mutations of 35% compared with 56% in the conventional fibroadenoma group. This is consistent with the findings of other studies which demonstrated a higher frequency of MED12 mutations in tumours with an intracanalicular growth pattern, which is usually not a feature of juvenile fibroadenomas. One study reported a higher incidence of MED12 mutations in juvenile fibroadenomas (52.6%).…”
Section: Discussionsupporting
confidence: 93%
“…Our cohort of 43 tumours was composed largely of conventional fibroadenomas and juvenile fibroadenomas, with no phyllodes tumours available for comparison. We found MED12 mutations in 46.5% (20 of 43) of the tumours, which is at the lower range of the rates of MED12 mutations reported in fibroadenomas (21–85.7%) . This could be due to the significant proportion of juvenile fibroadenomas (17 of 43) in our cohort, which showed a lower frequency of MED12 mutations of 35% compared with 56% in the conventional fibroadenoma group.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Here, we demonstrate that, unlike conventional FAs, >70% of which harbour MED12 mutations in the stromal (i.e. mesenchymal) components, non‐Carney complex‐related MFAs lack MED12 mutations, and no somatic mutations affecting the 410 cancer genes included in our sequencing assay are present at high mutant allele fractions. Moreover, apart from the PRKAR1A mutation in MFA6, selected pathogenic mutations affecting known cancer genes were found to be restricted to the epithelial components of these lesions.…”
Section: Discussionmentioning
confidence: 68%